The lantern's dance : [large type] a novel of suspense featuring Mary Russell and Sherlock Holmes - King, Laurie R. (King, Laurie R. Mary Russell novel., 2024)
"Mary Russell and Sherlock Holmes look forward to spending time with Holmes' son, Damian Adler, and his family. But when they arrive at Damian's house, they discover that the Adlers have fled. Holmes rushes after Damian while Russell stays behind to search the house. She discovers an old journal written in code and sets about deciphering the intricate cryptograph. It seems increasingly urgent that Russell figure out how the journal and lantern are related to Damian--and possibly to Sherlock Holmes himself. Could there be things about his own history that even the master detective does not perceive?"--